First Report of Middle Eocene Micromorphic Brachiopods from Northeastern Libya: Taxonomy and Paleobiogeography Implications - Sayed M. Abd El-Aziz; Ibrahim M. Abd El-Gaied; Mansour H. Al-Hashim; Maria Aleksandra Bitner; Yasser F. Salama; Petra Heinz; Mostafa M. Sayed (Diversity)
Two brachiopod species, Terebratulina tenuistriata (Leymerie, 1846) and Orthothyris pectinoides (von Koenen, 1984), have been recorded for the first time from the Middle Eocene (Late Lutetian) nummulitic limestone beds in the Darnah Formation at the Wadi Darnah area in Northeast Libya. These brachiopod species are associated here with Nummulites discorbinus (Schlotheim), Nummulites praelyelli (Boukhary and Kamal), and Nummulites bullatus (Schaub) and are widely distributed on this Middle Eocene Nummulites carbonate platform. The two recorded species are common in the Eocene rocks of Europe and the Arabian Gulf. In northern Africa, the brachiopod species Terebratulina tenuistriata (Leymerie) was only recorded from the Middle Eocene (Bartonian) of Egypt, while Orthothyris pectinoides (von Koenen) is firstly recorded from the Middle Eocene of the southern Tethyan Province (NE Libya) in the present work.